AN ANALYSIS ON THE INTERCONNECTION OF INTRANET AND INTERNET NETWORK AT REGIONAL SECRETARIAT OFFICE OF ACEH - Murthadha, M.; Fathiah, Fathiah (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
An internet network analysis is needed to understand the traffic on a network. This paper attempts to analyze some tests to find out the quality of the existing network at Regional Secretariat Office of Aceh. Browsing test and ping test were carried out for local, national, and international domain in order to know how much time does it takes to open a website considering those three servers have different distances. The download and upload speed tests were conducted to know how much times does it takes to download and upload a specific size file. This speed tests were performed using speedtest.net site to compare the bandwidth on Microtic router RB 1100 with unlimited bandwidth and Microtic router CCR 1016 with 10 Mbps bandwidth. The result of that comparison will be found out by three examiners using Laptop and Desktop. We hope that this paper will help all network administrators and further examiners in conducting a more detail analysis on other existing networks.Â Â Keywords: Browsing test, Ping test, Download and upload test